Use of free modified jejunal flaps to reconstruct pharyngoesophageal defects with preservation of the larynx in three cases. Issue 12 (14th May 2022) - Liu, Jifeng; Yu, Rong; Wang, Ji; Deng, Di; Li, Linke; Li, Bo; Liu, Jun; Chen, Fei
Abstract: The larynx is often sacrificed in patients with hypopharyngoesophageal cancer before reconstruction using the jejunum to restore the continuity of the digestive tract and allow oral alimentation. We retrospectively collected and analyzed data from three patients who underwent hypopharyngoesophageal reconstruction by partial patch and partial tube free jejunal flap with preservation of laryngeal function. All three flaps survived in patients who underwent the modified jejunal flaps. The larynx was preserved in all three patients. Partial patch and partial tube jejunal flap is a possible option for reconstruction of large and complex defects after pharyngectomy and cervical esophagectomy with larynx preservation. Abstract : The larynx is often sacrificed in patients with hypopharyngoesophageal cancer before reconstruction using the jejunum to restore the continuity of the digestive tract and allow oral alimentation. We retrospectively collected and analyzed data from three patients who underwent hypopharyngoesophageal reconstruction by partial patch and partial tube free jejunal flap with preservation of laryngeal function. All three flaps survived in patients who underwent the modified jejunal flaps. The larynx was preserved in all three patients. Partial patch and partial tube jejunal flap is a possible option for reconstruction of large and complex defects after pharyngectomy and cervical esophagectomy with larynx preservation.